(-)-Stepholidine blocks expression, but not development, of cocaine conditioned place preference in rats. (24th August 2020) - Bennett, A.; Barrera, E.; Namballa, H.; Harding, W.; Ranaldi, R.
Highlights: Dopamine D1 and D3 receptors play an important role in cocaine reward. Stepholidine blocks the expression of cocaine conditioned place preference. Stepholidine fails to block the development of cocaine conditioned place preference. Abstract: The purpose of this study was to investigate the effects of (-)-stepholidine (SPD), a compound with dopamine D1 partial agonist and D2/D3 antagonist properties, on the development and expression of cocaine conditioned place preference (CPP). Subjects ( N = 65; male Long Evans rats) were tested using a CPP procedure consisting of 3 phases: (1) a 15-min pre-exposure session where animals could explore each compartment freely, (2) eight 30-min conditioning sessions where animals were restricted to one side or the other with cocaine (10 mg/kg) or saline, respectively, on alternating days and (3) a 15-minute preference test session where animals could explore each compartment freely. To test the effects of SPD on expression of cocaine CPP, rats were administered vehicle (distilled water with 20 % DMSO), 10, 15 or 20 mg/kg SPD (intraperitoneally) 30 min prior to the test session. We found that 20 mg/kg of SPD significantly blocked the expression of cocaine CPP. To test the effects of SPD on the development of CPP, 0 (vehicle), 10, 15 or 20mg/kg SPD were administered 30 min prior to each cocaine conditioning session and vehicle before each saline conditioning session; no treatment was given prior to the test session. A preference test showed that each SPD group maintained a CPP similar to the vehicle group. These data indicate that SPD can block the expression of a cocaine CPP but has no effect on its development, suggesting that it inhibits the effects of cocaine cues on cocaine incentive motivated behavior. These results suggest that SPD may be a potential treatment for cue-driven aspects of cocaine use disorder.